2022
DOI: 10.1186/s12890-022-02030-x
|View full text |Cite
|
Sign up to set email alerts
|

Lung disease burden assessment by oscillometry in a systematically disadvantaged urban population experiencing homelessness or at-risk for homelessness in Ottawa, Canada from a prospective observational study

Abstract: Rationale Oscillometry is an emerging technique that offers some advantages over spirometry as it does not require forced exhalation and may detect early changes in respiratory pathology. Obstructive lung disease disproportionately impacts people experiencing homelessness with a high symptoms burden, yet oscillometry is not studied in this population. Objectives To assess lung disease and symptom burden using oscillometry in people experiencing hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Diving deeper into the available literature on post-infection oscillometry and pulmonary metrics in SARS-CoV-2 patients, several studies point towards the potential of oscillometry as a more sensitive measure of lung function impairment compared with traditional spirometry. A recent study by Pakhale et al [ 23 ] demonstrated the clinical utility of oscillometry in identifying persistent lung function abnormalities in patients with mild to moderate COVID-19 disease and who had normal spirometric results. Furthermore, according to a study by Frija-Masson et al [ 24 ], lung diffusion capacity, measured through single-breath diffusing capacity for carbon monoxide (DLCO), can also be impaired in COVID-19 patients, including those with mild disease who did not require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Diving deeper into the available literature on post-infection oscillometry and pulmonary metrics in SARS-CoV-2 patients, several studies point towards the potential of oscillometry as a more sensitive measure of lung function impairment compared with traditional spirometry. A recent study by Pakhale et al [ 23 ] demonstrated the clinical utility of oscillometry in identifying persistent lung function abnormalities in patients with mild to moderate COVID-19 disease and who had normal spirometric results. Furthermore, according to a study by Frija-Masson et al [ 24 ], lung diffusion capacity, measured through single-breath diffusing capacity for carbon monoxide (DLCO), can also be impaired in COVID-19 patients, including those with mild disease who did not require hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike spirometry, these exams require little cooperation [20][21][22], which can be an essential advantage for patients with PD.…”
Section: Introductionmentioning
confidence: 99%